2019
DOI: 10.1007/s00167-019-05502-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative latent medial laxity and correction angle are crucial factors for overcorrection in medial open-wedge high tibial osteotomy

Abstract: Purpose This study aimed to determine which preoperative factors affect the postoperative change in the joint line convergence angle (JLCA) by preoperatively quantifying soft tissue laxity. Methods Thirty-four patients who underwent medial open-wedge high tibial osteotomy (HTO) with a navigation were analysed. The JLCA change after HTO was calculated using standing long-bone anteroposterior radiographs taken preoperatively and 6 months postoperatively. Latent soft tissue laxity was defined as the amount of sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 32 publications
6
90
0
1
Order By: Relevance
“…The joint line convergence angle (JLCA) was defined as the angle between the tangent to the subchondral plates of the femoral condyle and the tibial plateau authors recommend to perform stress radiographs [27,35,38,45,48] because varus/valgus laxity appears to be important to predict influence of soft tissue laxity on alignment correction [35,38]. Lee et al proposed the concept of latent medial laxity by subtracting the JLCA on the weight-bearing standing radiograph from the JLCA on the valgus stress radiograph stress, this is thought to represent the ability of the soft tissue to stretch from a standing position to the valgus stress position [27]. To quantify the instability of the knee joint, other surgeons assessed the change in the JLCA (ΔJLCA) by the difference in JLCA between varus stress and valgus stress radiographs [45,48].…”
Section: Reviewmentioning
confidence: 99%
“…The joint line convergence angle (JLCA) was defined as the angle between the tangent to the subchondral plates of the femoral condyle and the tibial plateau authors recommend to perform stress radiographs [27,35,38,45,48] because varus/valgus laxity appears to be important to predict influence of soft tissue laxity on alignment correction [35,38]. Lee et al proposed the concept of latent medial laxity by subtracting the JLCA on the weight-bearing standing radiograph from the JLCA on the valgus stress radiograph stress, this is thought to represent the ability of the soft tissue to stretch from a standing position to the valgus stress position [27]. To quantify the instability of the knee joint, other surgeons assessed the change in the JLCA (ΔJLCA) by the difference in JLCA between varus stress and valgus stress radiographs [45,48].…”
Section: Reviewmentioning
confidence: 99%
“…Unexpected valgus overcorrection may be due to large preoperative JLCA in both OWHTO [10] and CWHTO [27]. A larger correction angle also affects overcorrection [25]. In the present series, CWHTO showed a greater ratio of JLCA change to the bony correction angle than OWHTO.…”
Section: Discussionmentioning
confidence: 44%
“…Dugdale et al have shown that total varus angulation of the OA knee was composed of three potential components: femorotibial geometric alignment, narrowing or loss of the osteocartilaginous complex, and separation of the lateral joint due to slack ligamentous and soft tissues [24]. Lower limb alignment after HTO is affected by soft tissue balance, as well as the bony correction angle [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Dugdale et al have shown that total varus angulation of the OA knee was composed of three potential components: femorotibial geometric alignment, narrowing or loss of the osteocartilaginous complex, and separation of the lateral joint due to slack ligamentous and soft tissues [24]. Lower limb alignment after HTO is affected by soft tissue balance, as well as the bony correction angle [25,26]. Unexpected valgus overcorrection may be due to large preoperative JLCA in both OWHTO [20] and CWHTO [27].…”
Section: Discussionmentioning
confidence: 99%